Simple and efficient synthesis of jasminaldehyde over modified forms of zirconia: Acid-base bifunctional catalysis - Kumar, T.; Shamshuddin, S.; Mujawar, Mubarak (2017)
© 2017, National Institute of Science Communication and Information Resources (NISCAIR). All rights reserved. The synthesis of jasminaldehyde over zirconia based acidbase bifunctional catalysts has beem reported. Solid catalysts such as zirconia, ceria and ceria-zirconia have been prepared and characterized for their physico-chemical properties such as surface area, surface acidity, surface basicity, crystalinity, functionality and elemental analysis by using techniques such as BET, NH 3 -TPD, CO 2 -TPD, PXRD, FT-IR and ICP-AES. The solid catalysts are evaluated in the aldol condensation of benzaldehyde and 1-heptanal to synthesize jasminaldehyde. Reaction conditions such nature of the catalyst, weight of the catalyst, molar ratio of the reactants, reaction temperature and reaction time have been studied to get a set of optimized reaction conditions under which highest possible yield of jasminaldehyde could be obtained. Reactivation and reusability of these solid catalysts is also studied. Ceria-Zirconia mixed oxide is found to be highly active and efficient bifunctional catalyst for the selective synthesis of jasminaldehyde. This catalyst is found to be reusable atleast for 6 reaction cycles without much loss of its catalytic activity.